Adenomatoid odontogenic tumor molecular pathogenesis: focusing on KRAS oncogenic mutations - Gomes, Isadora Pereira; Gomes, Carolina Cavalieri (Journal of Oral Diagnosis, 2025)
Adenomatoid odontogenic tumor is a rare benign odontogenic tumor, accounting for less than 10% of odontogenic tumors. It primarily affects young females and typically grows slowly, often in association with an unerupted permanent maxillary canine. Histologically, it contains rosette- or duct-like structures. A monoclonal tumor origin has been suggested and more recently KRAS mutations, particularly at codon 12, have been reported in a high proportion of cases. The occurrence of such mutations in adenomatoid odontogenic tumors is the focus of the present narrative review. The MAPK/ERK pathway is activated in adenomatoid odontogenic tumor, even in KRAS wild-type cases, suggesting that other mechanisms may lead to the activation of this pathway. Considering that the tumor usually exhibits an indolent clinical course with almost no risk of recurrence after conservative surgical treatment, the value of targeted therapies is unclear. The rarity of adenomatoid odontogenic tumor limits large-scale studies, but future research may reveal additional mutations and their role on its pathogenesis.